Izročilo in dediščina rokopisnih pesmaric v prekmurščini od 16. do 20. stoletja = The Tradition and Legacy of Handwritten Hymnals in Prekmurian Language from the 16th to the 20th Century - Dončec, Akoš Anton (Edinost in dialog, 2024)
In addition to printed books, Prekmurian Slovene language has a rich tradition of manuscripts (especially handwritten songbooks), which dates back to the 16th century. The preserved manuscript songbooks are mostly collections of religious, church songs; however, many mortuary songbooks can also be found. The first manuscript in Prekmurje was the socalled Prva Martjanska pesmarica (songbook), which was started by Protestants in the 16th century in the village of Martjanci (near Murska Sobota). The copyists included the songs from this songbook into their own manuscripts, and the songs spread everywhere between the Mura and the Raba. The tradition of songbooks continued in the 18th, 19th and 20th centuries. In the process of copying, various authors improved and added to the poems linguistically. Many of them were taken over by other authors in their printed prayer books and songbooks (e.g. Mikloš Kuzmič, Štefan Sijarto, Mihael Bakoš, Jožef Pustaj, Anton Števanec). Today some manuscripts are kept in archives or libraries, while others are still in private ownership. Several manuscripts were never recovered.